The Role of Traditional Islamic Boarding in Strengthening Human Resource Toward Indonesia 2045 at Islamic Boarding School - Malihah, Lola; Claudia, Meiske; Rahmawati, Rini (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine the role of Pondok Pesantren Darussalam Martapura, a traditional Islamic boarding school, in supporting sustainable national development by strengthening human resources toward the realization of Indonesia Emas 2045. A qualitative approach was employed using a case study design. Data were collected through in-depth interviews with key stakeholders, including pesantren leaders, administrative staff, teachers, and alums, and were complemented by observations and document analysis, then analysed using interactive qualitative analysis. The findings indicate that the pesantren plays a strategic role in human resource development by fostering a strong organizational culture and embedding character education into students' daily lives. Core values such as discipline, role modelling, and respect for knowledge serve as fundamental pillars in shaping students’ attitudes and behaviors. Furthermore, the pesantren contributes to the simultaneous development of intellectual, social, emotional, and spiritual intelligence. The integration of these dimensions produces individuals who are value-oriented, adaptable, and ethically grounded. These findings underscore the continued relevance of traditional pesantren as an effective model for strengthening human resources in support of Indonesia’s national development agenda toward Indonesia Emas 2045.